Sensitivity of geophysical techniques for monitoring secondary CO2 storage plumes. (February 2022) - Gasperikova, Erika; Appriou, Delphine; Bonneville, Alain; Feng, Zongcai; Huang, Lianjie; Gao, Kai; Yang, Xianjin; Daley, Thomas
Highlights: Assessment of sensitivity of seismic, EM, and gravity to deep secondary CO2 plumes. Assessment of detection thresholds of seismic, EM, and gravity. Advanced imaging of surface seismic data has great potential to locate secondary CO2 plumes. Borehole-to-surface EM or surface gravity are feasible for time-lapse monitoring of deep secondary CO2 plumes. Forward modeling approaches to evaluate post-injection monitoring configurations. Abstract: For geologic carbon storage, the ability to detect secondary CO2 plumes—defined as those CO2 plumes accumulating outside the intended storage reservoir—is fundamental to preventing unexpected CO2 migration into groundwater resources and for risk and liability management. Understanding the sensitivity of various geophysical methods to secondary plumes is crucial for designing cost-effective monitoring schemes. We use several modeling scenarios to demonstrate the process of assessing sensitivities and detection thresholds of three primary geophysical techniques—surface seismic, borehole-to-surface electromagnetic (EM), and surface and borehole gravity—for early detection of secondary CO2 plumes in the post-injection phase. While seismic reflection methods are often considered in monitoring strategies to track the evolution of CO2 plumes, they are also the most expensive. Due to cost considerations, especially for long-term post-injection monitoring, other techniques complement seismic monitoring when designing an adaptive monitoring network. Borehole-to-surface EM or surface gravity surveys are feasible for time-lapse monitoring of deep secondary CO2 plumes. These surveys could be carried at intervals defined by site-specific conditions. If time-lapse EM and/or gravity surveys detect any signal responses beyond the expected change, it would trigger a need for the higher resolution seismic survey.